Potential agrifood application of seriguela (Spondias purpurea L.) residues extract and nanoZnO as antimicrobial, antipathogenic and antivirulence agents (Research, Society and Development, 2022)
The impact of phytopathogenic microorganisms in several crops causes significant losses in agrifood industry, spoilage throughout food chain and storage. Nanoparticles and plant extracts have been highlighted by their antimicrobial properties applied in food packaging, agriculture, drug delivery systems and other medical approaches. Over the past few years, this group have studied the application of ZnO nanoparticles and agroindustrial wastes in edible food coatings/films. This study aimed to evaluate active characteristics from the extract of seriguela processing wastes and nanoZnO regarding to their inhibitory activity against bacterial pathogenicity and virulence systems TTSS (Type Three Secretion System) and QS (Quorum Sensing) for Pseudomonas savastanoi. Also, antibacterial action (inhibition area) against species of Curtobacterium, Clavibacter, E. coli, Xanthomonas and Serratia, and antifungal against Botrytis cinerea (reduction in colony size). The 60% extract inhibited the activation of QS and TTSS system in 20.26% and 13.54%, respectively; while nanoZnO at 3% reduced 46.77% QS and increased 302.88% TTSS. Extract without dilution inhibited the growth of Clavibacter michiganensis pv michiganensis (Gram-positive) and Xanthomonas phaseoli (Gram-negative), inhibitory zone of 94.25 mm2 and 452.39 mm2 respectively. The latter also being inhibited by nanoZnO 1 and 2% (138.23 mm2) and 3% (275.67 mm2). Pure extract inhibited 17.38% growth of fungal colony and nanoZnO (1 and 3%) in 33.08%. Finally, the active agents studied showed to be promising in the prevention of phytopathogenic diseases and consequently economic losses, food films/coatings and the extract as a biopesticide, reducing the environmental impact.